Leveraging the McGeer Criteria to Estimate the Frequency of Inappropriate Antibiotic Prescribing for Urinary and Respiratory Tract Infections Relative to the Onset of the COVID-19 Pandemic at a Skilled Nursing Facility - Paulina M. Colombo; Ferris A. Ramadan; Dilsharan Kaur; Darunee Armenta; Peter P. Patterson; Katherine D. Ellingson (Antibiotics)
Background/Objectives: The COVID-19 pandemic affected antimicrobial stewardship in healthcare, including Skilled Nursing Facilities (SNFs). This study aimed to (1) assess the appropriateness of antibiotic prescriptions for urinary tract infections (UTIs) and respiratory tract infections (RTIs) and identify predictors of inappropriate use; (2) analyze changes in prescribing practices relative to the pandemic’s onset. Methods: A retrospective review of electronic medical records from a 300-bed SNF (March 2019–March 2021) identified suspected UTIs and RTIs based on laboratory tests and antibiotic requests. Antibiotic prescription appropriateness was defined by clinical and microbiological alignment with the McGeer criteria, which are standardized infection definitions for long-term care residents, for UTI and RTI. Logistic regression models identified predictors of inappropriate prescribing, and an interrupted time-series analysis (ITS) examined trends relative to the pandemic onset (11 March 2020) in Arizona. Results: Among 370 antibiotic prescriptions, 77% of UTI and 61% of RTI prescriptions were inappropriate per the McGeer criteria. Acute dysuria and increased urgency were associated with lower odds of inappropriate UTI prescribing. For RTIs, a positive COVID-19 test increased the odds of inappropriate prescribing, while fever and acute functional decline lowered them. UTI prescriptions and inappropriateness overall increased during the pandemic, but no significant ITS trends emerged. For RTIs, no significant changes in prescribing or inappropriateness relative to the pandemic were observed. Findings emphasize the need for robust antimicrobial stewardship during and after public health emergencies.